Penerapan Metode TOPSIS Pada Sistem Pendukung Keputusan Untuk Menentukan Harga Jual Buah Mangga yang Berkualitas - Siswanto, Didik; Nijal, Lasri; Putra, Pandu Pratama (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Decision Support System (Decision Support System) is designed to produce a variety of alternatives offered to decision-makers, because most of the decision-making process that shapes the selection of alternatives to be selected, a particular mechanism, with the hope of producing a good decision. The method used for the selection of decision is Teqnique for Order Preferences by Similarity to Ideal Solution (TOPSIS) that can help find the optimum solutions or alternatives to a problem. This method can help decision makers in the situation where there are many alternative decisions with multiple criteria, to choose quality seeds of mango.